PELATIHAN WIRAUSAHA PEMBUATAN PENGHARUM RUANGAN BERNILAI EKONOMIS DI KALANGAN IBU RUMAH TANGGA KAMPUNG PENAS - Haro, Andrian; Nazir Ahmad , Gatot; A. W. S Waspodo, Agung; Aviyati , Friska (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2019)
To improve the capabilities and skills of housewives in Penas Kalimalang village, it can be done through training in entrepreneurship skills in making economic value fragrances and can serve as souvenir gifts. This skills training uses survey and interview methods as well as demonstration practices directly in front of participants. The number of participants participating was 22 housewives. The purpose of this study was to improve entrepreneurship skills of housewives in Penas Kalimalang Village through the manufacture of economically-priced air fresheners. With the presence of this training can help and develop the creativity, ability, and knowledge of housewives, especially in the area of ​​ Penas Kalimalang village to produce independently or in groups of air freshener products that have economic value and can be used as home industry businesses.